Leveraging Technology for Sustainable Logistics: Logistics Performance Index in Inland Ports with Eco Strategy and Sustainable Practices - Mohd Sharif, Kamal Imran; Yiaw, Michael Tio Boon; Ismail, Mohd Azril; Khand, Qamar Uddin; Hassan, Mohamed Ghozali; Shahron, Syairah Aimi (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The growing global awareness of sustainability and the recognition of interconnectedness across the world have elevated the significance of factors such as the Logistics Performance Index (LPI), Eco Strategy, and Sustainable Performance within the logistics and transportation sectors. Environmental and social responsibilities have firmly entrenched themselves at the forefront of both public and private corporate agendas. In the context of this research, the study delves deep into the examination of sustainable practices and eco strategies that exert a discernible influence on the Logistics Performance Index. This examination is facilitated through the collection of responses from top management personnel within inland ports, shedding light on the pivotal role of sustainable strategies in optimizing logistics performance. Moreover, to harness the transformative potential of technology and further bolster sustainable practices, logistics corporations are actively embracing the development of a state-of-the-art Dry Port Measurement Toolkit (DPMT). This innovative toolkit seamlessly integrates the crucial components of the Logistics Performance Index (LPI), Eco Strategy, and Sustainable Performance practices. It offers a comprehensive approach geared toward enhancing the environmental and social dimensions of logistics operations, ultimately fostering a more sustainable and responsible logistics industry.